Systematics, distribution and morphology of the newt parasitic water mites of the subgenus Lurchibates Goldschmidt & Fu, 2011 (Acari, Hydrachnidia, Hygrobatidae, Hygrobates Koch, 1837), including the description of four new species and a key to all so far known species - Goldschmidt, Tom; Nishikawa, Kanto; Hiruta, Shimpei F.; Pfingstl, Tobias; Jiang, Jian-Ping; Shimano, Satoshi (Zootaxa, 2021)
Four new water mite species of the genus Hygrobates, subgenus Lurchibates (Acari, Hydrachnidia, Hygrobatidae) are described. Hygrobates (Lurchibates) macrochela sp. nov. Goldschmidt, Nishikawa & Shimano is described in male and female; Hygrobates (Lurchibates) malosimilis sp. nov. Goldschmidt, Nishikawa & Shimano is described in male, both new water mite species were collected from newts of the species Pachytriton inexpectatus Nishikawa, Jiang, Matsui & Mo, 2011; Hygrobates (Lurchibates) incognitus sp. nov. Goldschmidt, Nishikawa & Shimano is described in female collected from newts of the species Paramesotriton guangxiensis (Huang, Tang and Tang, 1983); Hygrobates (Lurchibates) fragmentarius sp. nov. Goldschmidt, Nishikawa & Shimano is described in a single severely fragmented specimen (sex could not be determined) collected from a newt of the species Paramesotriton yunwuensis Wu, Jiang, and Hanken, 2010. Principal differences between the subgenus Lurchibates and the nominal subgenus Hygrobates s. str. are illustrated and discussed as well as the sexual dimorphism of Lurchibates. Morphometric analyses confirmed the morphological differences of ten out of the eleven so far described species (H. (L.) fragmentarius could not be included in the analysis); two morphological groups became evident mainly based upon the shape of the anterior coxae. These analyses as well provide an idea of possible phylogenetic relationships among the species. A key to all currently known species of the subgenus Lurchibates is given. So far the subgenus is restricted to SE-Asia, a map showing the distribution of all species is presented.